Scaling leadership building organizational capability and capacity to create outcomes that matter most - Anderson, Robert J. 1955-; Adams, W. A. (John Wiley & Sons, 2019)
This book, based on groundbreaking research, shows how senior leaders describe and develop leadership that works, that does not, that scales, and that limits scale. --
Includes bibliographical references and index. - Print version record
Keywords: Leadership